Global hotspots of mycorrhizal fungal richness are poorly protected - Van Nuland, Michael E; Averill, Colin; Stewart, Justin D; Prylutskyi, Oleh; Corrales, Adriana; van Galen, Laura G; Manley, Bethan F; Qin, Clara; Lauber, Thomas; Mikryukov, Vladimir; Dulia, Olesia; Furci, Giuliana; et al. (Nature, 2025)
Mycorrhizal fungi are ecosystem engineers that sustain plant life and help regulate Earth's biogeochemical cycles1-3. However, in contrast to plants and animals, the global distribution of mycorrhizal fungal biodiversity is largely unknown, which limits our ability to monitor and protect key underground ecosystems4,5. Here we trained machine-learning algorithms on a global dataset of 25,000 geolocated soil samples comprising >2.8 billion fungal DNA sequences. We predicted arbuscular mycorrhizal and ectomycorrhizal fungal richness and rarity across terrestrial ecosystems. On the basis of these predictions, we generated high-resolution, global-scale maps and identified key reservoirs of highly diverse and endemic mycorrhizal communities. Intersecting protected areas with mycorrhizal hotspots indicated that less than 10% of predicted mycorrhizal richness hotspots currently exist in protected areas. Our results describe a largely hidden component of Earth's underground ecosystems and can help identify conservation priorities, set monitoring benchmarks and create specific restoration plans and land-management strategies.
Keywords: půdní mikrobiologie; Biodiversity; mykorhiza; ekosystém; Conservation of Natural Resources; Soil Microbiology; strojové učení; biodiverzita; Mycorrhizae; Machine Learning; Ecosystem; zachování přírodních zdrojů